The Impact of Folding Shutter on the Daylighting Performance in Tropical Climate - Yasmine Mawaddag Ghufrona; Asri Dinapradipta; FX Teddy Badai Samodra (Institut Teknologi Sepuluh Nopember, 2020)
Utilization of abundant sunlight in tropical climates as daylighting can help to save energy consumption in the flats building. Based on daylight conditions in tropics, there is a need for a dynamic shading to be applied in façade which can be transformed to respond to the environmental change. Folding shutter is a dynamic shading device which can be operated by using folding and rotation motion. This paper aims to discuss the impact of folding shutter on the daylight performance in the context of flats buildings in tropical climates. Simulation using Radiance was conducted to test the sub-variables of folding shutter, including the folding configurations and shutter’s rotation angles on different conditions in tropics. The results showed that folding configurations results in high increase of daylight intensity and should be applied moderately. Meanwhile the shutter’s slats can help to diffuse and reflecting incoming light to the deepest areas of room. A closed configuration with shutter’s angle of 0° and 45° performed the best to face the inconsistent cloud movement in partly cloudy sky. The integration of folding shutter and 60 cm overhang produced the most stable performance which can meet the visual comfort standard in the longest period in tropics.